2013
DOI: 10.1097/bsd.0b013e3182621a05
|View full text |Cite
|
Sign up to set email alerts
|

Retrodental Mass in Rheumatoid Arthritis

Abstract: This article recognized 3 distinctive types of the retrodental mass in RA; type 1 (pannus), type 2 (pseudotumor), type 3 (mixed). It further concludes in all types of the retrodental mass associated with atlantoaxial subluxation secondary to RA, posterior fusion without decompression can achieve improvement of the myelopathy. In type 2 associated with vertical subluxation, on balance between calculable benefits and high risks of anterior transoral decompression, the authors prefer to opt for occipitocervical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…22,24 On the other hand, retro-odontoid pseudotumors in patients with RA are typically visualized as being hypo-to iso-intense on T1 and hyperintense on T2-weighted MRI. 7, [10][11][12]27 Yonezawa et al, 25 however, reported 3 types of retro-odontoid masses on MRI in patients with RA: pannus type (T1 low, T2 high), pseudotumor type (T1 low, T2 low), and mixed type (T1 low, T2 low and high). High signal intensity on T2-weighted images indicates that the pseudotumor consists of an increased amount of water, as in inflammatory tissue, and low signal intensity T2-weighted images indicates that the pseudotumor contains fibrous material.…”
Section: Discussionmentioning
confidence: 99%
“…22,24 On the other hand, retro-odontoid pseudotumors in patients with RA are typically visualized as being hypo-to iso-intense on T1 and hyperintense on T2-weighted MRI. 7, [10][11][12]27 Yonezawa et al, 25 however, reported 3 types of retro-odontoid masses on MRI in patients with RA: pannus type (T1 low, T2 high), pseudotumor type (T1 low, T2 low), and mixed type (T1 low, T2 low and high). High signal intensity on T2-weighted images indicates that the pseudotumor consists of an increased amount of water, as in inflammatory tissue, and low signal intensity T2-weighted images indicates that the pseudotumor contains fibrous material.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, neurological deterioration has also been reported to occur in the setting of rheumatic disease due to inflammatory involvement of the atlantoaxial articulation and retrodental pannus formation [4,12,17,19,20]. Although the cervical spine is a common site of rheumatoid disease manifestation, there is paucity of literature on isolated C1-C2 involvement, especially in the elderly population without evidence of previous rheumatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The most common type of incomplete spinal cord injury is central cord syndrome, which is characterized by a more severely impaired motor function in the upper than the lower extremities [1,8,10,13,16]. Progressive neurological deficit has also been reported to occur due to C1-C2 pannus formation in the setting of rheumatic disease [4,12,17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The critical mediators in RA are considered to be pro-inflammatory cytokines such as RANKL, TWEAK and granulocyte macrophage colony stimulating factor (GM-CSF) [ 17 19 ]. Progressive erosion of bone in the affected sites manifests as a pseudotumoral condition of the synovium called pannus where all these complex cascades of events occur [ 20 ].…”
Section: Introductionmentioning
confidence: 99%